Study of Cathode-Anode Spraying in a Gas Discharge Light-Sensitive System Based on CdTe-SnO2 - Utamuradova, Sharifa B.; Fayzullaev, Kakhramon M.; Khaydarov, Bunyodbek Z. (East European Journal of Physics, 2026)
This paper investigates the physical phenomena occurring in a gas discharge photosensitive system that uses cathode-anode sputtering. This system consists of a single-crystal cadmium telluride and a glass plate coated with SnO2, separated by a gas gap. The thickness of the gas gap is 100 µm. The materials under study are sputtered onto the glass plate’s surface in a vacuum chamber. Changes in the optical density of bismuth, tellurium, aluminum, and tin under the action of gas discharge are examined. It has been demonstrated that decreasing bismuth thickness results in a sharp increase in the ’current’ sensitivity of the gas discharge cell, reaching a value of qm = 10‑4 C/cm2 at an optical density of D = 0.5.